The role of communication and coordination between 'network lead companies' and their strategic partners in determining NPD project performance. (15th October 2008) - Badir, Yuosre F.; Buchel, Bettina; Tucci, Christopher
Using the data collected from three in-depth case studies of hightech New Product Development (NPD) projects conducted by network lead companies from different industries with alliance partners, we attempt to extend and merge the knowledge of NPD management, communication and coordination theory, and inter-organisation theory by proposing a contingency model. We propose that under conditions of fit between contextual factors that characterise high-tech NPD projects and the intensity level of communication and coordination, NPD project performance is highest. The model indicates that NPD project performance is contingent on the fit between the actual intensity level of communication and coordination – between the network lead company and its project's strategic partners – and the required intensity level. The required intensity of communication in uncertain and complex projects is dominated by the development cycle time of the project.